Clima social familiar y depresión en el adulto mayor - Gomez Floriano, Rosa Leslie Yanina (2016)
This descriptive correlational research, conducted in adults Mayor Adult Program at the Hospital Santa Isabel - El Porvenir, aimed to determine the level of depression and Level Family Social Climate Program in users. The sample consisted of 63 seniors. Geriatric Depression Scale Yesavage (GDS Geriatric Depression Scale =) and the Family Social Climate Scale was applied. For the analysis and interpretation of the results of the statistical test Chi Square was used. The results show that 42.9 percent have moderate level of depression, 65.1 percent indicates a level of family social climate and average 71.4 percent a level of family social climate under, has a level of severe depression. The results show significant values where the correlation between the level of family social climate and level of depression in older adults. It may show that the family is a very important role especially in the socio-affective relations, which are pimordiales for the elderly and psychological well-being and development a better quality of life. Keywords: Elderly, depression, family social climate.